ESTETIKA SENI KALIGRAFI ISLAM PADA KUBAH MASJID AGUNG AL-MUNAWWARAH KOTA JANTHO - Asdiana; Destri Wulanda; Alfikhairina Jamil (DESKOVI : Art and Design Journal, 2024)
Estetika yang mengkaji tentang keindahan akan menurun nilainya jika dikaitkan dengan kesenangan sensual atau duniawi. Sebaliknya, jika estetika dikaitkan dengan moral dan agama maka nilainya akan semakin tinggi. Kita dapat menemukan nilai estetika ini di dalam karya seni seperti karya Seni Kaligrafi atau Seni Khat. Seni Kaligrafi merupakan salah satu cabang seni rupa yang mampu memikat daya tarik seseorang dengan keindahan tulisannya. Dengan model Khat yang bermacam-macam Kaligrafi kemudian menjadi ornament bagi Masjid atau tempat-tempat suci lain dan menjadi bagian dari seni Arsitektur Islam. Macam-macam ukiran yang terdapat pada sisi dinding, tiang, bahkan atap Masjid menjadi Ikon ciri khas dari agama Islam. Kaligrafi mempunyai keistimewaan yang tidak dimiliki oleh karya seni lainnya. Khat murni lahir dari Seni Islam yang merupakan pengejawantahan firman Allah Swt yang suci. Tidak seperti karya seni lainnya yang mendapat pengaruh dari budaya non muslim seperti Musik, Arsitektur, Lukis dan lain sebagainya. Indonesia is a country rich in diversity, be it religion, ethnicity and culture. Aceh is one of the areas in Indonesia where the majority of the population is Muslim. This makes the Aceh region have many mosques with various shapes and beauty. The author will analyze the aesthetics of calligraphy at the Al Munawwarah Mosque in Jantho City. This mosque has a unique shape with a semicircular building with a very large dome. This study aims to examine the background of each calligraphy found on the inside of the dome of the Al Munawwarah Mosque in Jantho City. The research method uses a qualitative method by collecting data, direct observation of the research object and conducting interviews with sources from the mosque administrators and creators, collecting photo documentation. The results of this study indicate that on the dome of the Al Munawwarah Mosque in Jantho City there are 2 (two) types of calligraphy, namely tsuluts khat and kufi khat because they are easy to apply, especially on curved areas such as the area on the dome of the mosque. Using a dominant green color is preferred in Islam. Consists of the Al-Fatihah letter at the top which means umbrella and the main points of the contents of the Al-Quran as a guideline in our lives as Muslims. At the foot of the dome there is the Verse of the Chair as a reminder of the oneness of Allah SWT. And between the two are placed Asmaul Husna.